Electrically Amplified Circularly Polarized Luminescence by a Chiral Anion Strategy - Li, Zhong‐Qiu; Wang, Yu‐Duan; Shao, Jiang‐Yang; Zhou, Zeyang; Gong, Zhong‐Liang; Zhang, Chuang; Yao, Jiannian; Zhong, Yu‐Wu (Angewandte Chemie International Edition, 2023)
The development of circularly polarized electroluminescence (CPEL) is currently hampered by the high difficulty and cost in the syntheses of suitable chiral materials and the notorious chirality diminishment issue in electrical devices. Herein, diastereomeric IrIII and RuII complexes with chiral (±)‐camphorsulfonate counteranions are readily synthesized and used as the active materials in circularly polarized light‐emitting electrochemical cells to generate promising CPELs. The addition of the chiral ionic liquid (±)‐1‐butyl‐3‐methylimidazole camphorsulfonate into the active layer significantly improves the device performance and the electroluminescence dissymmetry factors (≈10−3), in stark contrast to the very weak circularly polarized photoluminescence of the spin‐coated films of these diastereomeric complexes. Control experiments with enantiopure IrIII complexes suggest that the chiral anions play a dominant role in the electrically‐induced amplification of CPELs. By using a chiral anion strategy, electrically amplified circularly polarized luminescence (CPL) is realized in light‐emitting electrochemical cells of readily obtained diastereomeric ionic transition‐metal complexes. The addition of a chiral ionic liquid (IL) into the active layer significantly improves the device performance and the electroluminescence dissymmetry factors.